Review of Carbonation Resistance in Hydrated Cement Based Materials - Marangu, Joseph Mwiti; Thiong’o, Joseph Karanja; Wachira, Jackson M. (Hindawi, 2019)
Blended cements are preferred to Ordinary Portland Cement (OPC) in construction industry due to costs and technological and environmental benefits associated with them. Prevalence of significant quantities of carbon dioxide (CO2) in the atmosphere due to increased industrial emission is deleterious to hydrated cement materials due to carbonation. Recent research has shown that blended cements are more susceptible to degradation due to carbonation than OPC. The ingress of CO2 within the porous mortar matrix is a diffusion controlled process. Subsequent chemical reaction between CO2 and cement hydration products (mostly calcium hydroxide [CH] and calcium silicate hydrate [CSH]) results in degradation of cement based materials. CH offers the buffering capacity against carbonation in hydrated cements. Partial substitution of OPC with pozzolanic materials however decreases the amount of CH in hydrated blended cements.Therefore, low amounts of CH in hydrated blended cementsmake them more susceptible to degradation as a result of carbonation compared to OPC. Themagnitude of carbonation affects the service life of cement based structures significantly. It is therefore apparent that sufficient attention is given to carbonation process in order to ensure resilient cementitious structures. In this paper, an indepth review of the recent advances on carbonation process, factors affecting carbonation resistance, and the effects of carbonation on hardened cement materials have been discussed. In conclusion, carbonation process is influenced by internal and external factors, and it has also been found to have both beneficial and deleterious effects on hardened cementmatrix.